Primary dermal melanoma: clinical behaviour, prognosis and treatment. Issue 11 (November 2020) - Harris, Christopher G.; Lo, Serigne; Ahmed, Tasnia; Scolyer, Richard A.; Ferguson, Peter M.; Karim, Rooshdiya Z.; Lam, Tai Khoa; Lee, Kenneth K.; Shannon, Kerwin F.; Spillane, Andrew J.; Stretch, Jonathan R.; Thompson, John F.; et al.
Abstract: Purpose: Primary dermal melanoma (PDM) is a subtype of cutaneous melanoma, confined to the dermis, which poses a challenging clinical dilemma. It may represent a true primary melanoma or a dermal cutaneous metastasis. This study aimed to delineate the histopathological characteristics and prognosis of PDM in a large patient cohort to guide appropriate treatment strategies. Methods: A search of the Melanoma Research Database at Melanoma Institute Australia was conducted to identify all possible PDM patients at our institution diagnosed from 1978 to 2013. Overall, melanoma-specific and disease-free survival outcomes of the PDM group were compared to those of similar cohorts of Stage I-II and Stage IV M1a melanoma patients based on propensity score matching. Results: Sixty-two PDM patients were identified from the MRD with a median follow-up of 6.3 years. Five-year survival was 87.1% and overall survival was 74.2%. PDMs had a significantly improved overall survival (p = 0.0002) and melanoma-specific survival (p = 0.001) compared to Stage I-II controls, however there was no difference in disease-free survival (p = 0.08). PDMs also demonstrated improved overall survival (p < 0.0001), melanoma-specific survival (p < 0.0001) and disease-free survival (p < 0.0001) compared to Stage IV M1a controls. Conclusion: These findings demonstrate that PDMs have a more favorable prognosis compared to stage I-II cutaneous melanomas and suggest that these are in fact true primary lesions. This study thus provides evidence to justify a treatment approach, by way of a wide local excision and possibly sentinel lymph node biopsy, as for early stage primary cutaneous melanomas.